Pengenalan Client Server dengan Metode Pembelajaran Demonstrasi pada Siswa Siswi SMA Hang Tuah 5 Sidoarjo - Edo Yonatan Koentjoro; Sulistiowati; Hardman Budiardjo; Henry Bambang Setyawan (Fakultas Ekonomi, Universitas PGRI Adi Buana Surabaya, 2023)
Client-server architecture is a software architecture concept that connects two objects in the form of a client system and a server system that communicate with each other via a computer network or the same computer. The knowledge of architecture needs to be introduced to students as general knowledge in entering Society 5.0, which helps students answer the challenges of social problems by utilizing various innovations that were born in the era of the industrial revolution 4.0. In responding to these challenges, Universitas Dinamika provides insight and knowledge through various materials to senior high school students and the local community who visit campus. One of the schools that visited and got insight into material related to client-server architecture was SMA Hangtuah 5 Sidoarjo. Through the demonstration learning method, an average level of understanding of participants was obtained at 77.4%. Participants gain a good understanding through direct practice during activities.